Occurrence of arbuscular mycorrhizal fungi in leaf litter and roots of shaded coffee plantations under organic and conventional management - Díaz-Ariza, Lucía Ana; Rivera, Emma Lucía; Sánchez, Natalia (Revista Brasileira de Ciência do Solo, 2020)
Evidence of arbuscular mycorrhizal fungal colonization of mat litter in various ecosystems plus previous reports of external mycelium of those fungi and mycorrhizal roots in litter from coffee plants and shade trees on coffee plantations suggest that they have a relationship with closed direct nutrient cycling between organic matter and living roots. This relationship was first proposed more than 50 years ago. Mycorrhizal symbiosis in tropical crops is affected by agricultural management practices. This study aimed to assess the occurrence of arbuscular mycorrhizal fungi in leaf litter from three shaded Colombian coffee agroecosystems under organic and conventional management. One is managed chemically, one organically, and one with a combined use of organic and chemical inputs. Leaf litter and roots were collected from the three coffee plots at three decomposition stages. Each plot represented a distinct fertilization and tree dominance pattern different from the other two plots. Arbuscular mycorrhizal fungi were found in decomposing leaves. The chemically managed plot showed statistical differences (p<0.05) with respect to the other plots, it had the greatest amounts of arbuscular mycorrhizal fungal root colonization (48.76–70.51 %), litter colonization (36.2–69.91 %), external mycelium length (28.66–48.33 m g -1 ), and spore number (451.27–681.2 spores in 20 g of dry soil). In contrast, conditions on the combined management coffee plot results in smaller means of the variables evaluated. Arbuscular mycorrhizal fungal root colonization and nitrogen content of leaf litter varied among the decomposition stages (p<0.05). Litter quality of different tree species may have influenced colonization of plant matter within each plot. We found evidence of typical structures of arbuscular mycorrhizal fungi within and among decomposing leaf litter and roots growing into the mat litter in tropical agroecosystems. This supports the thought that these fungi have a role in carbon and nutrient recycling, which are influenced by agricultural management practices and plant population composition.
Keywords: nutrient cycling; Coffea arabica; organic agriculture; agroforestry